(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
For a period of four months beginning in July 2020 and terminating in October 2020, weattempted to methodically evaluate the airborne fungal flora at Govt. College of Education with theobjective to determine their identification, concentration, and diversity in order to properly understandthe composition of the entire aeromycoflora. The study period was during the monsoon period, whichincluded mild to moderate temperature and high humidity, with ranges of 17.0-38.2°C and 26-92,respectively. After two weeks, an air sample was taken using the culture plate technique (CPT) on petridishes using Potato Destrose Agar (PDA) media. After a 3-5 day period of incubation at 25-28°C, thefungal colonies that emerged were identified according to micro and macro morphologicalcharacteristics followed by by the percentage contributions of individual species of fungi werecalculated.Altogether ten different kinds of fungal colonies, including Alternaria alternata, Asperillus niger,Alternaria tenussima, Cladosporium herbarum, Cladosporium cladosporioides, Curvularia lunata, andFusarium oxysporum, were found in outdoor environments. Deuteromycotina displayed dominance inthe overall spore contribution among all taxonomic categories.